AN ASSESSMENT OF THE IMPACT OF TRAINING AND DEVELOPMENT ON EMPLOYEE PERFORMANCE AND ENGAGEMENT - Saxena, Rajeev; Gupta, Dr. Avinash (South Eastern European Journal of Public Health, 2024)
This study looks at how 250 Rajasthan Rajya Vidyut Utpadan Nigam Limited employees' performance and employee engagement are affected by training and development (T&D) activities. The study attempts to look into the direct relationships between T&D and Employee Engagement and Performance using Structural Equation Modeling (SEM) and Maximum Likelihood estimation. The findings suggest that enhancing T&D programs can lead to improved organizational outcomes and higher levels of employee engagement. The study highlights the importance of strategic investments in employee development for organizational effectiveness, and it also points to areas that require further research on how to optimize T&D strategies for long-term workforce engagement and performance enhancement.